The Role of Fat Blends in Improving the Physicochemical Properties of Palm Kernel Oil for Monolaurin Synthesis - Ngatirah, Ngatirah; Hidayat, Chusnul; Rahayu, Endang Sutriswati; Utami, Tyas (Trends in Sciences, 2022)
This study aims to analyze the physicochemical properties of fat blends between palm kernel olein and stearin in different ratios. Furthermore, it determines the fat blends, which have more than 50 % lauric acid at the sn-2 position. The liquefied RBDPKOo (refined bleached deodorized palm kernel olein) and RBDPKOs (refined bleached deodorized palm kernel stearin) were mixed in proportions of 100:0; 80:20; 60:40; 40:60; 20:80; and 0:100 (w/w), and homogenized at 70 °C for 15 min. Also, the samples analyzed were fatty acid composition, triglyceride profile and physicochemical properties. The results showed the blending of RBDPKOo with RBDPKOs resulted in a change in melting point, iodine value, and behavior. Increased RBDPKOs resulted to a higher melting point, and a lower iodine value of fat blends. A blending with higher RBDPKOs (more than 60 %) resulted in a sharp endothermic peak. Meanwhile, blending of RBDPKOo with RBDPKOs significantly changes the fatty acid composition and triglycerides profiles. The RBDPKOs in the fat blends increased the trilaurin, and the composition as well as the amount of lauric acid at the position of sn-2. In addition, the 2 fat blends obtained with more than 50 % lauric acid at the position of sn-2 were RBDPKOo: RBDPKOs ratios of 40:60 and 20:80, respectively. HIGHLIGHTS Palm kernel olein and stearin blend Improving the Physicochemical Properties of Palm Kernel Oil Raw material of monolaurin synthesis